2023
DOI: 10.1177/0920203x231155148
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic diplomacy and patron–client relations in Sino-Serbian cooperation

Abstract: Since the outbreak of the COVID-19 pandemic, the authorities of Serbia have undertaken a concerted effort to secure China’s support in containing the coronavirus. This asymmetrical cooperation, apart from aspects concerning health security, has allowed both sides to obtain considerable political and economic benefits. This article examines how China and Serbia utilize pandemic cooperation to pursue and realize their wider foreign and internal policy goals through patron–client ties, as well as highlighting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In recent years, however, public opinion on China has become more negative due to its perceived role in the start of the global coronavirus pandemic (e.g., Neafie 2022) as well as increasing critical coverage of the BRI (Yang and Van Gorp 2023). Still, in Serbia, the pandemic seems to have strengthened bilateral relations (Kowalski and Rekść 2023), signalling the established resilience of BRI strategic communication in this country (Mitić 2017), which makes it a notable case to study the potential drivers of public perceptions.…”
Section: Public Perceptionmentioning
confidence: 99%
“…In recent years, however, public opinion on China has become more negative due to its perceived role in the start of the global coronavirus pandemic (e.g., Neafie 2022) as well as increasing critical coverage of the BRI (Yang and Van Gorp 2023). Still, in Serbia, the pandemic seems to have strengthened bilateral relations (Kowalski and Rekść 2023), signalling the established resilience of BRI strategic communication in this country (Mitić 2017), which makes it a notable case to study the potential drivers of public perceptions.…”
Section: Public Perceptionmentioning
confidence: 99%
“…Not putting all of its eggs in one basket is in actuality how Serbia has been conducting its foreign policy for nearly 15 years. It has strived to walk the fine line of not siding with either Western or Eastern global powers, particularly in light of the strained rivalry between actors such as the USA and China, or the EU and Russia (Kowalski and Rekść, 2023; Ushkovska, 2022). While heavily criticised for its friendship with Beijing, Serbia’s openness for doing business with everyone has served it well during the pandemic as by January 2021 the country already boasted having enough vaccines for its entire population.…”
Section: Sino-serbian Synergymentioning
confidence: 99%
“…Despite the fact that the factory, once built, never truly began production due to the global decline in demand for COVID-19 vaccines by 2022, the laying of foundations was marked with diplomatic and media fanfare. Coupling Chinese public diplomacy with the unbridled accolades by Serbia’s political leadership of China as Serbia’s ‘sole saviour’ (Kowalski and Rekść, 2023) has unsurprisingly impacted public opinion in the country toward Beijing. A survey by the Central European Institute of Asian Studies demonstrated that China’s image among Serbians had improved over the course of 3 years (Gledić et al, 2021), indicating that much of it can be attributed to China’s pandemic-time performance.…”
Section: Sino-serbian Synergymentioning
confidence: 99%
“…Recently, the study of patron-client relationships has become increasingly important, both in the disciplines of anthropology, economics and politics (Kowalski & Rekść, 2023;Sayarı, 2014). This is evidenced by the many discussions about patron-clients by several disciplines.…”
Section: Introductionmentioning
confidence: 99%